Optimization of HCAR1 and binding partners for cryo-EM studies - von Brömsen, Lucas (My University, 2022)
The G protein-coupled receptor HCAR1 has recently been linked to several different types of cancer, and silencing of this gene has led to decreased cancer cell growth and proliferation. In a clinical setting and structure-based drug design, the structure of this protein would be of immense importance for drug development; no experimental structures of HCAR1 have been determined however. This study aimed to investigate a novel method, the Nb6 method, that utilizes a nanobody for obtaining the inactive-state structure of the receptor. In parallel, a conventional experiment for obtaining the active-state structure of the receptor by using a G protein was performed. The results concluded that there was a major difference in expression and stability of HCAR1 depending on what host system was used. Additionally, a stable and pure form of HCAR1 was obtained in large quantities by using the BacMam system. The nanobody was also purified in large quantities, the purity was however of questionable quality. Complex formation of HCAR1 and the nanobody was evaluated but it was determined that optimization of all processes needed further improvement and no definitive conclusion as to if there was an interaction between HCAR1 and the nanobody could be deduced. HCAR1 in combination with G protein for obtaining the active-state structure could not be obtained in a stable form, though this was likely due to the host system this protein was expressed in. Several implementations are suggested as to how to improve purification and stability of the proteins which would result in stable proteins suitable for structural determination with cryo-EM.
Keywords: HCAR1; GPR81; lactate receptor; Nb6; BacMam; GPCR